A marker band folgen stratigraphy for the Cenomanian Chalk of England and its extension to northen Germany and France - Jeans, Christopher Vincent (Acta Geologica Polonica, 2023)
A novel stratigraphical scheme within the Folge Concept is described for the Cenomanian Chalk of England that is particularly suitable for investigating the regional changes in the lithofacies, diagenesis, geochemistry, and mineralogy of the sediments of the Chalk Sea leading up to the Cenomanian–Turonian Oceanic Anoxic Event. It is based on “isochronous” marker bands defined largely by calcitic macrofossil assemblages, and it avoids problems caused by the poor or non-preservation of ammonite assemblages and lateral changes in chalk lithofacies. Eight folgen are based on one, two, or more marker bands. Their sequences, lithologies and calcitic macrofossil assemblages are described from 33 exposures in the Northern Chalk Province of England. The folgen are named, in ascending order, the Belchford, Stenigot, Dalby, Bigby, Candlesby, Nettleton, Louth and Flixton, after villages in Lincolnshire and Yorkshire, England. The folgen are traced throughout the Transitional and Southern Chalk provinces of England. They are present in the Cenomanian chalk of northern Germany and northwest France. Regionally, an individual folge may display considerable vertical and lateral variation in general lithology and lithofacies whilst still maintaining their defining marker bands. The possibility of further refinement to the scheme is discussed.
Keywords: Cretaceous; Cenomanian chalk; Folge stratigraphy; Marker bands; England; Northern Germany; Northwest France; Cenomanian–Turonian Anoxic Event